A simple supramolecular assay for drug detection in urine. Issue 63 (21st July 2017) - Sonzini, Silvia; McCune, Jade A.; Ravn, Peter; Scherman, Oren A.; van der Walle, Christopher F.
Abstract : A supramolecular colorimetric assay utilising the macrocyclic host cucurbit[7]uril with a commercial dye molecule, neutral red, was evaluated as a novel method for drug detection in urine of a model therapeutic peptide drug Octreotide. Abstract : A supramolecular colorimetric assay utilising the macrocyclic host cucurbit[7]uril (CB[7]) with a commercial dye molecule, neutral red (NR), was evaluated as a novel method for drug detection in urine of a model therapeutic peptide drug Octreotide.